UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KEMAMPUAN BACAAN AL-QUR’AN PADA SISWA DI SMP NEGERI 2 PULO ACEH - Hasanah Hasanah (Jurnal Dedikasi Pendidikan, 2017)
This study entitled " The Effort of Islamic Education Teachers in Improving Students’ Reciting Al- Qur'an Ability at SMP Negeri 2 Pulo Aceh." This study uses quantitative methods. This study aims to determine the efforts of teachers PAI in improving the capability which was achieved by students in reciting the Qur'an from class VII, VII and IX. The total sample of this study is 58 students. From the observation, it was known that the student’ reciting Al-Qur’an ability of SMP Negeri 2 Pulo Aceh is not maximized as desired. However, the teachers have been working to make their students can properly recite Al-Qur’an by providing extra tutoring or hours beside PAI subjects, and the teachers also give advice to the students to be diligent and active in studying the Al-Qur'an.